Sliding Wear of Copper-Impregnated Carbo-Graphite Under Different Conditions - Mahto N.K.; Tyagi R.; Mishra S. (My University, 2025)
Keeping in view the importance of carbo-graphite materials in sealing applications in aircraft engines, the tribological performance of carbo-graphite (CG) and copper-impregnated carbo-graphite (Cu-CG) has been evaluated at different temperatures (RT to 350 °C) under dry and (RT and 120 °C) oil-lubricated conditions. The results indicate that CG exhibited a lower coefficient of friction due to the presence of a graphite-rich tribo-film that facilitated easy shearing at the contact interface. The wear rate of both the materials increased with temperature and Cu-CG showed a lower wear rate compared to CG, due to its higher hardness caused by the impregnation of copper. Under oil-lubricated conditions, Cu-CG exhibited a lower coefficient of friction and wear rate at RT and 120 °C compared to CG. This has been attributed to the reduction in open pores, which allowed the entrapment of oil between surface asperities to hold higher pressure, resulting in an increased hydrodynamic action. © ASM International 2024.